Alternative splicing related genetic variants contribute to bladder cancer risk. Issue 8 (27th April 2020) - Guo, Zheng; Zhu, Huanhuan; Xu, Weidong; Wang, Xi; Liu, Hanting; Wu, Yanling; Wang, Meilin; Chu, Haiyan; Zhang, Zhengdong
Abstract: Emerging evidence has shown that aberrant alternative splicing (AS) events are involved in the carcinogenesis. The association between genetic variants in AS and bladder cancer susceptibility remains to be fully elucidated. We searched for single nucleotide polymorphisms (SNPs) which are located in splicing quantitative trait loci (sQTLs) in bladder cancer through CancerSplicingQTL database and the 1000 Genomes Project. A case‐control study including 580 cases and 1, 101 controls was conducted to assess the association between the functional genetic variants and bladder cancer risk. Next, we used GTEx, TCGA, and GEO databases conducting sQTL analysis and gene expression differences analysis to evaluate the potential biological function of the candidate SNPs and related genes. We found that SNP rs4383 C>G was remarkably related with the reduced risk of bladder cancer (odds ratio = 0.68, 95% confidence interval = 0.59‐0.79, P = 3.91 × 10 −7 ). Similar results were obtained in codominant, dominant and recessive model. Stratified analyses revealed that the effect of SNP rs4383 C>G on bladder cancer was more significant in the older subjects (age > 65), female and nonsmokers. sQTL analysis showed that SNP rs4383 was associated with the AS events of its downstream gene MAFF with a splicing event of alternative 5′ splice site. The messenger RNA expression of MAFF in bladder tumor tissues was lowered compared with normal tissues. Patients with high expression of MAFF had higher survival rates. These findings indicated that SNP rs4383 related with the AS events of MAFF was associated with bladder cancer risk and could represent a possible biomarker for bladder cancer susceptibility.